Manager for Health-Buzzword or Necessity for Companies - Šarotar Žižek, Simona; Veingerl Čič, Živa; Šebjan, Urban (Anali PAZU HD, 2022)
Human capital is an invisible property that contributes to higher innovation, productivity and employability and represents an individual characteristic of the individual, regardless of age bracket. The importance of human capital in the company have already in 1995 confirmed the analysis of the World Bank, which show that human capital represents in highly developed countries, an average of 67% of the total wealth of the country and is higher than the share of physical capital. Therefore is the aging of people, together with the care for their health and well-being a significant challenge; its management or non-management will have economic and social consequences. One way of managing health and safety at the workplace and wellbeing is certainly the design of the function of manager for health of in the company, whose concern will be related to activities that are focused to human (employee), on his body, soul and spirit. The basic task of manager for health are investments in increased employee health motivation, encouraging working atmosphere and increasing of social competencies.
Keywords: health; psychical well-being; employee; manager for health; health promotion